Effects of hotel characteristics on room rates in Porto: a hedonic price approach - Castro, Conceição (2015)
According to the hedonic price method, a price of a good is related with the characteristics or the services it provides. Within this framework, the aim of this study it is to examine the effect on room rates of different characteristics of hotels in and around the city of Porto, such as star category, size, room and service quality, hotel facilities and location. It was estimated a hedonic price function, using data for 51 hotels. The results enable to identify the attributes that are important to consumers and hoteliers and to which extent. This information can be used by hotel managers to define a price strategy and helpful in new investment decisions.